Poverty, the middle class, and income distribution amid COVID-19 - Jose Ramon G. Albert; Michael Ralph M. Abrigo; Francis Mark A. Quimba; Jana Flor V. Vizmanos (Philippine Institute for Development Studies (PIDS), 2020)
Often development focus has been on measuring and analyzing poverty in order to reduce poverty. While the poor face future prospects of being perpetually trapped in poverty, the nonpoor also are vulnerable to poverty. Vulnerability has been particularly recognized in the wake of the impact of the novel coronavirus (COVID-19) that is likely to yield declines in incomes because of reduced economic activities. In this study, we provide an updated profile of the poor in the Philippines, as well as various segments of the income distribution, based on the 2018 Family Income and Expenditure Survey. We follow the typology of the low, middle and high income classes proposed in previous research reports, and simulate the likely effects of contractions in per capita income on poverty and the entire income distribution amid the coronavirus pandemic. In estimating the impact of COVID-19 on poverty, and the income distribution, data are not available at this time. The study makes use of simulation scenarios and assumptions. We find that in a (medium case) scenario of declines of incomes by 10 percent across the entire income distribution, the number of poor Filipinos can increase by 5.5 million, but with the emergency financial subsidies (i.e., the social amelioration program and the small business wage subsidy in. place) that targeted 90 percent of households, the worsening of poverty conditions has been managed so that only 1.5 million would fall into poverty, i.e., 4 million less than expected number of Filipinos falling into poverty. These simulation results are consistent with nowcasting exercises of IFPRI and the World Bank on poverty amid COVID-19 that assume a global GDP contraction of 3 percent. Further, low-income classes would, on average, transition only a quarter year more than the baseline of 21.25 years for this (medium-case) scenario if after the pandemic (and an assumed V-shaped economic recovery), their incomes would have a constant annual growth of 2.5 percent. However, under tougher conditions of income contractions of 20 percent with social protection cash assistance, we simulate that the average time for low income Filipinos to move up into middle income class would increase by three years from baseline figures. [...]
Keywords: 330; poor; middle class; inequality; income distribution; novel corona virus; simulation